Sistem Informasi Pemasaran Hasil Pertanian Polinela Berbasis JSON - Dwirgo Sahlinal; Rima Maulini; Dewi Kania Widyawati (Institut Informatika dan Bisnis Darmajaya, 2018)
Agricultural information system aims to build a marketing system based on JSON information system technology (Java Script Object Notation). Specifically the research aims: (1) build a database using JSON; (2) establish marketing information system of agricultural products; (3) provide information on the implementation of identification, inventory monitoring of agricultural product marketing issues. The research begins with literature review, planning and preparation of system model, model verification, field trial, evaluation and development and implementation result. Output targets to be generated: (1) basic data of agricultural product marketing processing; (2) built a marketing information analysis system with JSON-based information technology.Keywords: Information System; Marketing; Agricultural Product; JSON.